Automotive Materials: An Experimental Investigation of an Engine Bay Acoustic Performances. (November 2016) - Siano, D.; Viscardi, M.; Panza, M.A.
Abstract: In this work an extensively experimental analysis aimed to verify the sound insulation properties of the engine bay of a commercial passenger car is carried out, evaluating the possibility to adopt different sound absorbing materials, to be applied under engine cover nylon skin, in the place of commonly used polyurethane foams. Experimental tests were performed on the vehicle at different stationary operating conditions, employing typical pressure microphones for far field measurements, according to the related prescribed standards. A limited number of materials has been initially selected through a preliminary analysis, and then employed for creating different engine cover configurations, which were subsequently tested in real engine operating conditions. For a good understanding of the obtained results, an experimental investigation through an innovative in situ impedance method aimed to assess acoustic properties of each considered material has been also performed. Among all the tested materials, only one able to ensure better acoustic performance at mid and high frequencies with respect to the already existing cover configuration, has been finally identified, after considering other selection criteria such as an adequate high temperature resistance and the most cost-effective solution. Future analyses will regard investigations on the use of additional materials, for solving problem in attenuating engine noise also at low frequencies.